Przeszłość i współczesność w twórczości Iriny Ratuszyńskiej - Rudziewicz, Irena (Studia Rossica Posnaniensia, 2012)
Russian poet Irina Ratushinskaya’s poetic output was presented in the article by paying attention to two aspects in her creativeness. The subject of the past is connected with Polish roots, Polish subject matter, religion and faith. Elements of contemporaneousness аre found in works about constraint, persecution, the fight for democracy and freedom, and describing the lack of agreement to restrict an individual`s freedom.